Microstructure and thermodynamics of polymer and surfactant systems - Dai, Sheng (2008)
In this thesis, the interaction between uncharged polymers and surfactants were systematically studied using the isothermal titration calorimetric (ITC), surfactant selective electrode (EMF), and laser light scattering (LLS) techniques, where the results provide the necessary information for the discovery of appropriate binding mechanisms.